Men or Machines - TUC leaflet about automation, 1936 (1936)
1936 1918-1939 "Men or Machines - TUC leaflet about automation, 1936" [T0162.jpg], 1936, Trades Union Congress The increasing use of automation and machinery generally in the 1930s was perceived as a threat to employment and control over the work process. This TUC leaflet demands a larger share of the benefits of increased output through innovation, with a shorter working week, a shorter working life and compensation to redundant workers.